A10.11 Expression of Unfolded Protein Response Genes in Synovium and Blood Mononuclear Cells of HLA-B27 Positive Ankylosing Spondylitis Patients is not Increased Compared to other Arthritis Patients and Healthy Controls. (25th February 2013) - Neerinckx, Barbara; Carter, Shea; Lories, Rik J
Abstract : Background: The HLA-B27 heavy chain is prone to misfolding. Misfolded proteins give rise to endoplasmic reticulum stress and activation of the Unfolded Protein Response (UPR). The UPR is strongly activated in HLA-B27 transgenic rats, an animal model for ankylosing spondylitis (AS), suggesting a role for HLA-B27 misfolding in the pathogenesis of the human disease and the UPR has been linked to IL23 production. Aim of the Study: To study endoplasmic reticulum stress and activation of the UPR ex vivo in the synovium and peripheral blood mononuclear cells (PBMCs) of HLA-B27 positive AS patients as compared to patients with other inflammatory joint diseases and healthy controls. Materials and Methods: Synovial tissues were obtained from actively inflamed knees from patients with AS (HLA-B27 positive), other forms of spondyloarthritis (SpA) (HLA-B27 positive or negative), rheumatoid arthritis (RA) (HLA-B27 positive or negative) and other inflammatory joint diseases ('non SpA/RA inflammatory joint disease') (HLA-B27 positive or negative) (n = 10 in each group). PBMCs were isolated from whole blood samples taken from patients with AS (HLA-B27 positive), RA (HLA-B27 negative) and healthy controls (HLA-B27 negative) (n = 12 in each group). Activation of the UPR in all samples was analysed using quantitative RT-PCR with primers for DDIT3 (also known as CHOP), HSPA5 (also known as BiP), DNAJB9 and XBP1s. Gene expression levels were correlated to disease activity scores such as DAS28, ASDAS, BASDAI as well as to CRP levels. Results: None of the UPR associated genes was specifically upregulated in either the blood cells or synovial tissue from AS patients as compared to the other groups. In the synovial samples, only DDIT3 expression was found significantly different between healthy controls and HLA B27 negative SpA patients on the one hand and non-SpA/RA inflammatory joint disease on the other hand. There was no significant difference in expression of HSPA5, DNAJB9 and XBP1s between the different groups. In PBMCs, expression of DDIT3 was different between groups and levels were significantly lower in the AS group compared to the RA group and the healthy controls. There was no difference in expression of the other genes between the groups. Discussion: Our data do not provide support for a critical and unique role of the UPR in AS and other forms of SpA. The difference in expression of DDIT3 in PBMCs with an increase in RA patient samples compared to AS patient samples suggests specific involvement of this gene in RA.